Greenstick fracture of the mandible: A case report - Kalia V; Singh A (Wolters Kluwer Medknow Publications, 2008)
This case report is an insight in to pediatric traumatology whereby bilateral greenstick fracture of condyle is used as a means to discuss the incidence and anatomic considerations for the management of the same, highlighting the fact that dental surgeons require a unique understanding of the anatomy, growth considerations, healing pattern and operative management involving minimal manipulation while managing pediatric facial fractures.